PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING TERHADAP SELF ESTEEM SISWA KELAS VIII DI SMP NEGERI 4 BANYUWANGI - Mutmainnah Afkarina; Harwanti Noviandari; Harjianto Harjianto (STKIP PGRI SUMENEP, 2023)
This research is motivated by the problem of low self-esteem in class VIII students at SMP Negeri 4 Banyuwangi. This study aims to determine the effect of group guidance services using role playing techniques on the self-esteem of class VIII students at SMP Negeri 4 Banyuwangi. This research is a quantitative experimental research using pre-experimental research methods with the type of one group pretest and posttest design. The population of this research is 192 students. The sample in this study were 14 students who were taken using a purposive sampling technique. Data collection tools used are observation, interviews, questionnaires and documentation.The results of the study showed that students' self-esteem scores were given after being given group guidance treatment using the role playing technique with an average pretest score of 63.28 in the low category and a posttest score of 92.92 in the medium and high categories. Based on the results of the sig.(2-tailed) value in the t-test it is known that it is 0.000 ? 0.05. On the basis of these calculations, Ha (alternative hypothesis) reads